Sustainable Urban Bus Service Assessment and Tourists’ Satisfaction - Syazwan Baharum; Suria Haron; Siti Zaharah Ishak; Syahirah Mansor (International Journal of Supply Chain Management, 2019)
This paper evaluates sustainable urban bus service quality based on passenger perception and expectation in local tourism destinations in order to attain a comprehension of tourists’ attitudes towards local public transport. The study focuses on the combination of route 101 and 102 by Rapid Penang bus to investigate passenger satisfaction because the bus is the main public transport used by most tourist who use both routes. Data collection by questionnaire survey from 201 valid questionnaires was analysed using sustainable assessment model for both routes. The focus groups of this study are local and foreign tourist as the perceived service quality has a significant positive influence on tourist satisfaction. Moreover, previous experience moderates the relationship between perceived service quality and satisfaction. Results obtained indicate 28 indicators in measuring performance of service quality offered, and 6 vital attributes are identified including; reliability, understanding, accessibility, physical facilities, environment and safety. Gap value obtained are sorted according to worst factor ranking wherein reliability (-1.094), safety (-1.076), physical facility (-1.029), understanding (-1.023), accessibility (-0.792) and environment (-0.772) respectively. This factors have significant effect on overall tourist satisfaction assessment. The findings of this study aims to suggest some interesting implications for practitioners and researchers based on factors that considered important by tourists.